Ethical communication of teacher in student character education at state junior high school of Bogor City - Suhifatullah, M. I.; Thoyib, Mastur (ARKA INSTITUTE, 2022)
In general, this research is to obtain data about the ethical communication of teachers in character education of students at state junior high schools of Bogor City. Specifically this research is to obtain data related to the 5 characteristics of teacher ethical communication in character education which include; (1) openness, (2) empathy, (3) supportive attitude, (4) positive attitude, and (5) equality. This study uses a descriptive quantitative method with a survey technique with a questionnaire instrument. The study population involved teachers from 3 public junior high schools in the city of Bogor totaling 137 people. Through the Slovin formula with an error of 5%, a sample of 102.05 was obtained which was rounded up to 100 teachers who were taken randomly and proportionally. The results of the study are as follows; (1) openness of teachers in communicating with students by 51.45% is included as the moderate category; (2) the empathy of teachers in communicating with students is 49.10% included as the moderate category which tends to be less good; (3) teacher supportive attitude in communicating with students by 51.30% included as the moderate category; (4) the positive attitude of teachers in communicating with students is 49.25% included as the moderate category which tends to be less good; and (5) the equality of teachers in communicating with students is 51.25% included as the moderate category. Then the accumulation of each of the aspects or indicators mentioned above is obtained the data showing that the ethics of teacher communication in character education of students at state junior high schools of Bogor City is 50.47% which is included as the moderate category.